Intercontinental's best of China - Law, Eugene (Beijing : China Intercontinental Press, 2008)
"An extensive guide of the various regions of China, broaching language, customs, foods, and daily life in addition to the various sites profiled"--Provided by publisher.
Includes index.
Keywords: China -- Description and travel; China -- Guidebooks